Islamic Political Literacy and Leadership through Mosque-Based Learning: A Community Engagement Program at TPA/TPSA Qiraatul Huda, Nagari Parambahan, Tanah Datar Regency - Dewi Dahlan; Jilan Annisa Usman; Dona Marsa Zuliyarni (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2026)
This community engagement program was initiated in response to limited Islamic political literacy and the lack of structured Islamic leadership development at TPA/TPSA Qiraatul Huda, Jorong Silabuak, Nagari Parambahan, Tanah Datar Regency. These conditions have constrained students’ understanding of Islamic socio-political values and limited their opportunities for meaningful social participation. The program aimed to enhance Islamic political literacy, foster proactive leadership character, and strengthen the role of the mosque as a center for community education and development. A participatory-educational approach was employed through a combination of workshops, a leadership camp, deliberation simulations and role-play activities, and mentoring for the development of learning modules. Program outcomes were evaluated using a mixed-method approach, combining quantitative measures through pre- and post-tests with qualitative data obtained from observations and interviews. The results indicated positive changes in students’ participation, understanding, and leadership-related attitudes. Participation rates during the activities ranged from 85% to 95%. Post-intervention assessment showed that 90% of the students demonstrated improved understanding of the values of shiddiq (honesty) and amanah (responsibility). Furthermore, 78% were able to explain the concept of shura by providing concrete examples, while 82% demonstrated an improved understanding of the role of a just leader in everyday activities. Beyond these learning outcomes, the program contributed to revitalizing the mosque as an inclusive space for socio-religious education and created a more structured environment for character and leadership development among young learners at the local level. The program demonstrates the potential of mosque-based learning to integrate Islamic political literacy, leadership education, and character development within community-based religious education.